Transient and Sub-transient Electrical Parameters based Classification of Micro Grids - Kr. Das, Tapash; Banik, Ayan; Chattopadhyay, Surajit; Das, Arabinda (International Journal of Computer Sciences and Engineering, 2025)
This work deals with transient and sub-transient nature of electrical parameters based classification of micro grid. Various type of models used in micro grid system using IGBT/Diodes, MOSFET / Diodes, GTO/Diodes, Ideal Switches, Switching – function based VSC, Thyristor, Diodes, Average-Model Based VSC have been studied. Different useful electrical parameters like voltage, current, active power, reactive power, etc have been monitored and their sub transient and transient behavior have been analyzed at normal load condition. Based on the observation, attempt has been taken to classify different types of present day micro grid systems with respect to sub-transient and transient nature of those useful electrical parameters. The study may be useful for modeling, synchronization, protection and performance analysis of various micro grid systems.